Towards an Interreligious Engagement: A Case Study of Paguyuban Eklasing Budi Murko (PEBM) in Kulon Progo, Yogyakarta - Suheri Suheri; Haris Fatwa Dinal Maula (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
The feeling of being the majority often drives people to hegemony other minorities. The presence of religious minorities seems marginalized because they do not have much power to assert their existence. This study examines the dynamic relationship between Paguyuban Eklasing Budi Murko (PEBM) followers and the religious majority in the Salamrejo. Thus, this research uses two theories: the indigenous religion paradigm and the non-formal interfaith dialogue. The research data is collected from an in-depth interview, literature studies, and mainstream online data. The hegemony assumption reveals that the feeling of the majority continues dominating society. In contrast, the hypothesis is too general. The relationship of PEBM as the indigenous religion and world religions community, particularly Islam, does not reflect this hypothesis. The dynamic relationships between PEBM and the majority groups in the village of Salamrejo are engaging with one another, which is influenced by two factors: First, Mbah Mangun is the elder and the most respected person in PEBM. Second, by the teachings of PEBM per se, which is very fluid to all religions in the paradigm of inter-subjectivity and interreligious engagement as a new strategy for PEBM to encourage social acceptance.